Common ragweed (Ambrosia artemisiifolia L.) causes severe yield losses in different soybean varieties by reducing the infection potential of Bradyrhizobium japonicum - Hall, Rea Maria; Wagentristl, Helmut; Karrer, Gerhard; Winter, Anna; Czerny, Robert; Kaul, Hans-Peter (Julius-Kühn-Archiv, 2020)
Ambrosia artemisiifolia L. (Asteraceae) known as common ragweed is an annual herbaceous species native to North America which has become one of the economically most important weeds in agricultural areas throughout Middle Europe. Its large ecological amplitude enables the species to establish in several types of environment, but management options to effectively contain its spread are limited due to lack of efficacy, cost and time or lack of awareness. In the last decade especially soybean fields were severely affected by ragweed invasion, but until now information on the yield-decreasing effects of the plant are scarce for Middle Europe. Therefore, the aim of the study, conducted in 2017 and 2018 as a greenhouse and biennial field trial, was an evaluation of the competition effects of ragweed upon 1) growth (aboveground/belowground), 2) infection potential of rhizobia and 3) yield of two different soybean varieties. Results revealed that on plots with the highest ragweed biomass the yield loss accounted for 83.7% on average. Particularly, the numbers of nodules as well as the mean weight of the nodule, which stand in tight correlation with soybean yield, were significantly reduced by the presence of ragweed. Only one ragweed plant per square metre reduced the number of nodules by 55.8% and consequently led to a decrease in yield of 18%.